Ventilatory Limitation of Exercise in Pediatric Subjects Evaluated for Exertional Dyspnea - Pianosi, Paolo T.; Smith, Joshua R. (Frontiers in Physiology, 2019)
Purpose Attribution of ventilatory limitation to exercise when the ratio of ventilation (V ̇E) at peak work to maximum voluntary ventilation (MVV) exceeds 0.80 is problematic in pediatrics. Instead, expiratory flow limitation (EFL) measured by tidal flow-volume loop (FVL) analysis – the method of choice – was compared with directly measured MVV or proxies to determine ventilatory limitation. Methods Subjects undergoing clinical evaluation for exertional dyspnea performed maximal exercise testing with measurement of tidal FVL. EFL was defined when exercise tidal FVL overlapped at least 5% of the maximal expiratory flow-volume envelope for >5 breaths in any stage of exercise. We compared this method of ventilatory limitation to traditional methods based on MVV or multiples (30, 35, or 40) of FEV1. Receiver operating characteristic curves were constructed and area under curve (AUC) computed for peakV ̇E/MVV and peakV ̇E/x∙FEV1. Results Among 148 subjects aged 7-18 years (60% female), EFL was found in 87 (59%). Using EFL shown by FVL analysis as a true positive to determine ventilatory limitation, AUC for peakV ̇E/30∙FEV1 was 0.84 (95% CI 0.78-0.90), significantly better than AUC 0.70 (95% CI 0.61-0.79) when 12-second sprint MVV was used for peakV ̇E/MVV. Sensitivity and specificity were 0.82 and 0.70 respectively when using a cutoff of 0.85 for peakV ̇E/30∙FEV1 to predict ventilatory limitation to exercise. Conclusion PeakV ̇E/30∙FEV1 is superior to peakV ̇_E/MVV, as a means to identify potential ventilatory limitation in pediatric subjects when FVL analysis is not available.